1976
DOI: 10.1111/j.1365-2141.1976.tb03575.x
|View full text |Cite
|
Sign up to set email alerts
|

Acquired von Willebrand Syndrome with Inhibitors Both to Factor VIII Clotting Activity and Ristocetin‐Induced Platelet Aggregation

Abstract: A case of acquired von Willebrand's syndrome (vWs) is described which appeared to be due to antibodies directed against factor VIII clotting activity (FVIIIC), factor VIII-related antigen (FVIIIRAg) and von Willebrand factor. The antibodies directed against FVIIIRAg was demonstrated by the inhibitory effect of a platelet eluate on Ristocetin-induced aggregation of normal platelets. This effect was not shown by the patient's platelet-poor plasma alone, nor could it be demonstrated in platelet eluates from 13 ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

1978
1978
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(20 citation statements)
references
References 16 publications
0
20
0
Order By: Relevance
“…In the case reported here, the acquired von Willebrand's syndrome was associated with a monoclonal gammopathy without evident lymphoproliferative or autoimmune disease. An abnormal response to factor VIII concentrate infusion was described in most of the cases (Mant et al, 1973;Handin et al, 1976;Stableforth et al, 1976;Rosborough and Swaim, 1978;Gazengel et al, 1978). Recovery of injected factor VIIIAHF was generally poor and without the sustained rise usually observed in patients with congenital von Willebrand's disease (Chediak et al, 1977).…”
Section: Inhibitory Effect Of Patient's Purifiedmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case reported here, the acquired von Willebrand's syndrome was associated with a monoclonal gammopathy without evident lymphoproliferative or autoimmune disease. An abnormal response to factor VIII concentrate infusion was described in most of the cases (Mant et al, 1973;Handin et al, 1976;Stableforth et al, 1976;Rosborough and Swaim, 1978;Gazengel et al, 1978). Recovery of injected factor VIIIAHF was generally poor and without the sustained rise usually observed in patients with congenital von Willebrand's disease (Chediak et al, 1977).…”
Section: Inhibitory Effect Of Patient's Purifiedmentioning
confidence: 99%
“…Recovery of injected factor VIIIAHF was generally poor and without the sustained rise usually observed in patients with congenital von Willebrand's disease (Chediak et al, 1977). Of the cases in which in-vitro evidence of an inhibitor was found, three had inhibitory activity against ristocetin cofactor alone (Leone et al, 1974;Handin et al, 1976;Wautier et al, 1976), while in one case inhibitor was also directed against factor VIIIAHF (Stableforth et al, 1976) and in another against factor VIIIAg (Gazengel et al, 1978). In those cases in which immunoglobulins were purified, the inhibitor was found either in the IgG fraction (Handin et al, 1976;Gazengel et al, 1978) or in the IgA fraction (Wautier et al, 1976) but never in the IgM fraction.…”
Section: Inhibitory Effect Of Patient's Purifiedmentioning
confidence: 99%
“…Proposed mechanisms for this disorder have included immunological inactivation of vWF [5,17], impaired release of vWF from storage sites, increased proteolysis of a qualitatively abnormal protein, and adsorption of vWF by tumour tissue. It has been suggested that the tumour may secrete a plasma factor, such as hyaluronic acid, which interacts with vWF and causes decreased serum factor levels [3,12].…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, antibodies with coagulation factor inhibitor activity have been eluted from the patient's platelets; this eluate inhibited normal ristocetin-induced platelet aggregation, therefore confirming that the antibodies are directed against vWF. 27,28 The electrophoretic pattern of vWF:Ag is used to determine quantitative and/or qualitative abnormalities in its multimeric structure. The most common anomaly is a defect in the high molecular weight multimers, either by a decrease in their number or by an abnormal structure similar to that seen in type 2 congenital vWD.…”
Section: Discussionmentioning
confidence: 99%